The HETDEX Survey: Probing Neutral Hydrogen in the Circumgalactic Medium of ∼88,000 Lyα Emitters - Mahan Mirza Khanlari; Karl Gebhardt; Laurel H. Weiss; Dustin Davis; Erin Mentuch Cooper; Mahdi Qezlou; Maja Lujan Niemeyer; Robin Ciardullo; Donald P. Schneider; Shiro Mukae; Chenxu Liu; Daniel Farrow; et al. (The Astrophysical Journal)
We explore the neutral hydrogen (H i ) gas around 1.9 <  z  < 3.5 Lyman alpha emitters (LAEs) from the Hobby–Eberly Telescope Dark Energy Experiment using faint Ly α absorption. This absorption is the result of H i in the halo of the LAE scattering Ly α photons from the integrated light of background galaxies along the line of sight. We stack millions of spectra from regions around ∼88,000 LAEs, in order to focus on the physics of the gas at large radii. The extensive number of fiber spectra contributing to the stacks ensures a sufficient signal-to-noise ratio to detect the faint Ly α absorption, which would otherwise be buried within the noise. We detect absorption out to a projected ∼350 kpc around an average LAE at z ∼ 2.5. We use these results to create an empirical radial W _λ (Ly α ) profile around LAEs. Comparison with numerical simulations reveals a profile similar to the empirical one within this region. Compared to previous studies, the profile is similar but modestly higher. We also outline a simple physical picture motivated by the observed trends in the data. We plan to quantify this radial profile as a function of redshift, local density, and Ly α luminosity, to explore the relationship between LAE environments and H i distribution.